Formation and properties of a terpyridine-based 2D MOF on the surface of water. (13th May 2016) - Koitz, Ralph; Hutter, Jürg; Iannuzzi, Marcella
Abstract: Two-dimensional networks inspired by graphene are of prime importance in nanoscience. We present a computational study of an infinite molecular sheet confined on a water surface to assess its properties and formation mechanism. Terpyridine-based ligand molecules are interlinked by Zn ions to form an extended 2D metal-organic framework. We show that the network is stable on the water surface, and that the substrate affects the dynamic properties of the sheet, exhibiting a confining effect and flattening the sheet by 30%. We use metadynamics to characterize the process of network formation and breaking and determine an intra-network binding energy of 143 kJ mol −1 . Based on this mechanistic insight we propose that the 2D network strength can be tuned by varying the rigidity of the ligand through its chemical structure.